2016
DOI: 10.9790/3013-067034362
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal plants with cardiovascular effects (part 2): plant based review

Abstract: Abstract:-Previous researches revealed that many medicinal plants affected cardiovascular function and can be utilize for therapeutic purposes. This review will highlight the cardiac, cardioprotective, vascular, hypolipidemic, fibrinolytic and anti platelet aggregating of medicinal plants as a second part of our previous review.Keywords : medicinal plants, herbs, cardiac, cardioprotective, vascular, hypolipidemic, [30]. This review was designed to cover the cardiac, cardioprotective, vascular, hypolipidemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Garlic also inhibits metastasis by preventing the binding of circulating cancer cells to the blood vessel walls (Wei et al, ). It was observed that the garlic extract restricted the growth of many cancers including breast, bladder, skin, colon, esophagus, stomach, and lung cancers (Al‐Snafi, ; H. A. R. Suleria, Butt, Khalid, et al, ). The results of these studies showed that the beneficial and anticancer effects of garlic had a direct relationship with the release of OSCs and allicin (C 6 H 10 S 2 O), as well as the DADS (C 6 H 10 S 2 ) production capacity (Mathan, Singh, & Singh, ).…”
Section: A Sativummentioning
confidence: 99%
“…Garlic also inhibits metastasis by preventing the binding of circulating cancer cells to the blood vessel walls (Wei et al, ). It was observed that the garlic extract restricted the growth of many cancers including breast, bladder, skin, colon, esophagus, stomach, and lung cancers (Al‐Snafi, ; H. A. R. Suleria, Butt, Khalid, et al, ). The results of these studies showed that the beneficial and anticancer effects of garlic had a direct relationship with the release of OSCs and allicin (C 6 H 10 S 2 O), as well as the DADS (C 6 H 10 S 2 ) production capacity (Mathan, Singh, & Singh, ).…”
Section: A Sativummentioning
confidence: 99%
“…The vasorelaxant activity of echinacoside, a phenylethanoid glycoside isolated from Cistanche tubulosa, and its possible underlying mechanism on isolated rat thoracic aortic rings pre-contracted with phenylephrine (PE, 1 microM) and KCl (60 mM) was investigated. Echinacoside (30-300 microM) exhibited an acute relaxation in endothelium-intact rings in a concentration-dependent manner, while this relaxation was significantly inhibited in endothelium-denuded condition and in the presence of the endothelial nitric oxide synthase (eNOS) inhibitor, N (W)-nitro-L-arginine methyl ester (L-NNA, 100 microM), an unselective soluble guanylate cyclase blocker, methylene blue (10 microM) and the selective sGC inhibitor 1 H- [1,2,4] oxadiazolo [4,3-A]quinoxalin-1-one (ODQ, 1 microM); in addition, atropine (1 microM), a selective muscarinic receptor antagonist, partially affected the relaxation. However, the cyclooxygenase inhibitor indomethacin (5 microM) had no influence on the relaxant action.…”
Section: Cistanche Tubulosamentioning
confidence: 99%
“…Vascular endothelium releases many vasoactive substances, which regulated and maintained the overall cardiovascular homeostasis. The previous studied showed that many medicinal plants possessed hypotensive effects and affected vascular activity either by direct effect on vascular smooth muscles or indirectly by affecting endothelium vasoactive substances (1)(2)(3) . The current review highlighted the medicinal plants with hypotensive and vascular effects as promising future therapies because of efficacy and safety.…”
Section: Introductionmentioning
confidence: 99%
“…The center of origin of saffron crop is not clear, as earlier Middle East (Asia Mi Turkestan and Iran) was considered as its center of origin [39], whereas, later on, C Treatment with ethanolic extract of saffron, was seen to have antiproliferative effect by significantly reducing the longevity of malignant carcinomic human alveolar basal epithelial cells [23]. Saffron derivatives having higher anti-carcinogenic potential has attributes of increased apoptosis, reduction in blood vessels [24], inhibiting RNA and DNA synthesis [25] and regulating lipid peroxidation and antioxidant activity [26].…”
Section: Center Of Origin and Geographical Distribution Of Saffron Cropmentioning
confidence: 99%